2016
DOI: 10.1080/0284186x.2016.1175659
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose rate brachytherapy with I-125 seeds has an excellent 5-year outcome with few side effects in patients with low-risk prostate cancer

Abstract: Out data confirmed that absorbed dose is a predictive factor for BFFS for low-risk patients without androgen deprivation therapy. With our treatment routines and dosimetry, a D90% in the range of 170-180 Gy gives excellent outcomes with acceptable toxicity for patients with low-risk prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…SBRT delivered to 35–37.25 Gy in 5 fractions provides a BED of >198 Gy resulting in greater coverage of the CTV and a more conformal and homogeneic dose distribution compared to brachytherapy. Our 5-year bRFS for low- (98.5%) and intermediate-risk (95.5%) patients are comparable to those reported for high dose conventionally fractionated radiation therapy and low-dose brachytherapy (3537). Further follow-up of PCa patients treated with SBRT will be required to confirm long-term cancer control suggested by its low PSA nadir.…”
Section: Discussionsupporting
confidence: 79%
“…SBRT delivered to 35–37.25 Gy in 5 fractions provides a BED of >198 Gy resulting in greater coverage of the CTV and a more conformal and homogeneic dose distribution compared to brachytherapy. Our 5-year bRFS for low- (98.5%) and intermediate-risk (95.5%) patients are comparable to those reported for high dose conventionally fractionated radiation therapy and low-dose brachytherapy (3537). Further follow-up of PCa patients treated with SBRT will be required to confirm long-term cancer control suggested by its low PSA nadir.…”
Section: Discussionsupporting
confidence: 79%
“…Conversely, Rasmusson et al . [ 4 ] found a significant relationship between D 90 and biochemical failure-free survival, with 167 Gy considered as the tipping point. However, in our present case series, we did not stratify for arbitrary dose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several institutions have reported 5- and 10-year biochemical relapse-free survival ranging from 94-96% [ 2 , 3 , 4 ] to 87-98.5% [ 3 , 5 , 6 , 7 ], respectively. In addition, a number of reviews have demonstrated that LDR brachytherapy is equally effective as EBRT or radical prostatectomy (RP) alone in patients with newly diagnosed low- or intermediate-risk prostate cancer [ 8 , 9 , 10 ]; however, Rodrigues et al .…”
Section: Purposementioning
confidence: 99%
“…Given this situation, ED is an important morbidity factor for patients treated with PB. 3,4 Previous studies reported that ED occurred in 40-85% of patients treated with PB, and this wide range was attributed to differences in patient backgrounds, questionnaire scores in sexual function evaluations, surgical techniques and follow-up intervals. 5,6 To amend this discrepancy, we carried out a longitudinal prospective study to examine sexual function in patients receiving PB monotherapy without neo-or adjuvant hormone therapy using the IIEF-15.…”
Section: Introductionmentioning
confidence: 99%